Utilizing 3D GIS for the sustainable management of UNESCO World Heritage Sites in Saudi Arabia - Ezz, Mohamed Salah; Soliman, Ashraf M.; Aldelgawy, Mohammed; Salem, Doaa A. H.; Khalil, Ragab (Frontiers in Built Environment, 2025)
IntroductionSpatial analysis documentation and visualization achieve through Geographic Information Systems (GIS) handles essential functions for heritage asset management. The research develops a 3D GIS platform that supports Al-Ahsa heritage building conservation as a UNESCO World Heritage Site through advanced spatial technology.MethodsThe collection of data occurred via historical record indexing together with stakeholder dialogue methods. The developed 3D GIS system merges heritage data of multiple categories including general and historical and urban elements along with architectural aspects and structural construction records through a structured relational database. Into this system researchers combined spatial analytics through GIS with web-mapping functions and three-dimensional modeling for telecommuting purposes and group decision-making features.ResultsThe developed system generated high-quality three-dimensional models together with crucial spatial information for preservation needs. The system enabled better understanding of cultural and historical components during urban planning tasks and architectural reviews. Through this platform building-structural data could be accessed precisely to conduct risk assessments that supported resource management decisions.DiscussionHeritage site management receives improved benefits because of 3D GIS platforms which unite various types of data into a unified framework. This approach demonstrates scalability that makes it suitable for expanded use in heritage preservation projects.ConclusionThe application of 3D GIS technology represents a beneficial element enabling heritage preservation through systematic record-keeping while offering visual representations and risk monitoring features. This technology demonstrates potential use as basis for building future protection strategies in heritage preservation.